Emerging Dual-Functional 2D transition metal oxides for carbon capture and Utilization: A review. (15th September 2022) - Yang, Liuqingqing; Heinlein, Jake; Hua, Cheng; Gao, Ruixia; Hu, Shu; Pfefferle, Lisa; He, Yulian
Graphical abstract: Highlights: A critical comparison of the conventional CO2 capture and utilization technology and the advanced integrated system is provided. An emerging class of two-dimensional transition metal oxides is presented as potential high-performance dual-functional materials in the integrated CO2 capture and utilization technology. Common two-dimensional transition metal oxides and their composites are summarised with their specific synthetic strategies and unique features. Abstract: Today, the atmospheric carbon dioxide (CO2 ) concentrations have reached an unprecedented record high of almost 420 ppm since the industrial revolution, resulting in an increase of the average global temperature by 1.5 °C. Tremendous efforts are being made to reduce carbon emission e.g. at stationary point sources such as fossil fuel-based power plants via CO2 capture and utilization (CCU) technologies. Pilot demonstrations of carbon capture using amine-based solvent have shown potential, but suffer from high operational costs and low thermodynamic efficiency, motivating researchers towards more cost-effective measures, such as integrated carbon capture and utilization (ICCU) systems. Here, a solid, dual-functional material (DFM) is used to capture CO2 and convert it into value-added chemicals/fuels in-situ . Such integrated systems eliminate the most energy & capital-demanding upstream operations, such as stripping, compression, and transportation. ICCU technologies also possess a much higher energy efficiency through effective heat utilization by leveraging the high temperature of the flue gas to supply the reaction enthalpies. The graduation of ICCU technology from academia to commercial applications requires the development of stable and high-performance DFMs that are not only capable of selectively capturing CO2, but also catalyzing CO2 into value-added products at reasonable temperatures. Most DFMs explored to date are characterized by a physical combination of CO2 adsorbers and catalysts, however such ensembles intrinsically contain limitations from the diffusion of CO2 from the adsorptive sites to the catalytic ones. In the present review, we present an emerging class of 2 dimensional (2D) materials, transition metal oxides (TMOs), to be explored as potential high-performance DFMs, where the adsorptive and catalytic sites are in close proximity. 2D TMOs have been extensively studied in both CO2 capture and catalysis fields, but their utilizations as DFMs for ICCU applications are just starting to be studied. We provide a comprehensive summary of typical 2D TMOs and their composites with specific synthetic strategies and unique features for CCU related applications. Although research on 2D TMOs as DFMs is still in an early stage, we hope that this review will inspire more demonstrations of 2D TMOs utilized in ICCU systems, with the ultimate goal to reduce CO2 emissions.